THE ROLE OF SOCIO-EDUCATIONAL INCLUSION IN SUPPORTING YOUTH MENTAL HEALTH AMID WAR-INDUCED UNCERTAINTY (Psychology Travelogs, 2025)
The article presents an empirical study on the role of socio-educational integration in supporting the mental health of young people amid war-induced uncertainty. It has been found that among persons with disabilities, the most resonant life resources are primarily social connections, a sense of belonging, social support, as well as life philosophy, faith, personal beliefs and moral values, cognitive strategies, imagination, dreams, and memories. In conditions of uncertainty caused by the war, it is essential that the promotion of positive content for social integration be approached as an imperative and sustained effort. Socio educational inclusion is one of the significant conditions of mental health, which testifies to the capabilities of the personality functioning, the team even in such conditions due to multidisciplinarity and an integrated approach built on the actualization of multidimensional resourcefulness.
Keywords: socio-educational integration; mental health; life resources; uncertainty due to the war; young people; people with disabilities